Six-year Burden of Care for Nonsyndromic Unilateral Cleft Lip and Palate Patients: A Comparison Between Cleft Centers and Noncleft Centers. (January 2023) - Janssen, Pierce L.; Ghosh, Kanad; Klein, Gabriel M.; Hou, Wei; Bellber, Christopher S.; Dagum, Alexander B.
Objective: To determine differences in burden of care between nonsyndromic patients with unilateral cleft lip and palate undergoing treatment at American Cleft Palate-Craniofacial Association (ACPA)-accredited centers and nonaccredited centers in New York State. Design: A retrospective review of the New York Statewide Planning and Research Cooperative System database from January 2001 to December 2014 was performed using ICD-9 and CPT coding. Patients, participants: This study included patients with unilateral cleft lip and palate who underwent both lip and palate repairs during their first 6 years of life. Exclusion criteria included orofacial cleft syndromes, follow-up under 6 years, and one-stage combined cleft lip and palate repairs. Results: Eighty-eight patients were treated at cleft centers, and 29 patients at nonaccredited centers ( n = 117). Age at primary palatoplasty (13.0 months vs 18.1 months; p = .019), total number of cleft operations (2.3 vs 2.7; p = .012), and total number of primary cleft-specific procedures (2.2 vs 2.5; p = .0049) were significantly lower for patients treated in cleft centers. Age at primary cheiloplasty (4.8 months vs 4.6 months; p = .865), post-cheiloplasty length of stay (1.2 days vs 1.2 days; p = .673), post-palatoplasty length of stay (1.5 days vs 1.9 days; p = .211), average hospital admissions (2.2 vs 2.3; p = 0.161), and total complication rates (34.1% vs 21.1%; p = 0.517) did not differ significantly between cleft centers and noncenters. Conclusions: This data demonstrates some significant differences in overall 6 year burden of care for nonsyndromic patients with unilateral cleft lip and palate treated at ACPA-accredited cleft centers versus nonaccredited centers.